ChemInform Abstract: Water Enhanced Synthesis of gem‐Bisphosphonates via Rh(I) Mediated 1, 4‐Conjugate Addition of Aryl Boronic Acids to Vinylidenebisphosphonate Esters. Issue 27 (13th June 2013) - Bianchini, Giulio; Scarso, Alessandro; Chiminazzo, Andrea; Sperni, Laura; Strukul, Giorgio
Abstract The employment of water as the solvent is crucial to substantially improve the yields with a wide range of boronic acids (II) and esters (IV) bearing various functionalities.